Adobe Premiere Pro 2.0. (Classroom in a book., 2006)
The most comprehensive way to learn Adobe Premiere Pro! Classroom in a Book, the best-selling series of hands-on software training workbooks, helps you learn the features of Adobe software quickly and easily. Classroom in a Book offers what no other book or training program does--an official training series from Adobe Systems Incorporated, developed with the support of Adobe product experts. Adobe Premiere 2.0 Classroom in a Book contains fourteen lessons and a bonus DVD with lesson files. The book covers the basics of learning Adobe Premiere Pro, and countless tips and techniques to help you become more productive with its new features, including new multicam editing tools, auto-creation of menu-based DVDs from the timeline, and Native HD, SD and HDV support, and more. You'll learn how to work with audio, create transitions and titles, manipulate subclips and virtual clips, and more. You can follow the book from start to finish or choose only those lessons that interest you.